Parallel Computational Technologies 16th International Conference, PCT 2022, Dubna, Russia, March 29-31, 2022, Revised Selected Papers - Sokolinsky, Leonid; Zymbler, Mikhail (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book constitutes the refereed proceedings of the 16th International Conference on Parallel Computational Technologies, PCT 2022, held in Dubna, Russia, during March 29-31, 2022. The 22 full papers included in this book were carefully reviewed and selected from 60 submissions. They were organized in topical sections as follows: high performance architectures, tools and technologies; parallel numerical algorithms; supercomputer simulation.
High Performance Architectures, Tools and Technologies -- VGL Rating: a Novel Benchmarking Suite for Modern Supercomputing Architectures -- HPC TaskMaster - Task Efficiency Monitoring System for the Supercomputer Center -- Constructing an Expert System for Solving Astrophysical Problems Based on the Ontological Approach -- HPC Resources of South Ural State University -- Parallel Numerical Algorithms -- Comparative Analysis of Parallel Methods for Solving SLAEs in Three-Dimensional Initial-Boundary Value Problems -- Optimization of the Computational Process for Solving Grid Equations on a Heterogeneous Computing System -- Parallel Methods for Solving Saddle Type Systems -- Compact LRnLA Algorithms for Flux-based Numerical Schemes -- Analysis of Block Stokes-Algebraic Multigrid Preconditioners on GPU Implementations -- Implementation of the Algebraic Multigrid Solver Designed for Graphics Processing Units Based on the AMGCL Framework -- Measuring the Effectiveness of SAT-based Guess-and-Determine Attacks in Algebraic Cryptanalysis -- Tuning of a Matrix-Matrix Multiplication Algorithm for Several GPUs Connected by Fast Communication Links -- Visualizing Multidimensional Linear Programming Problems -- Supercomputer Simulation -- Quantum-Chemical Calculations of the Enthalpy of Formation of Some Tetrazine Derivatives -- A New Approach to the Supercomputer Simulation of Carbon Burning Sub-Grid Physics in Ia Type Supernovae Explosion -- Parallel Simulations of Dynamic Interaction between Train Pantographs and an Overhead Catenary Line -- Construction of a Parallel Algorithm for the Numerical Modeling of Coke Sediments Burning from the Spherical Catalyst Grain -- MPI-based PFEM-2 Method Solver for Convection-Dominated CFD Problems -- Modeling of Two-Phase Fluid Flow Processes in a Fractured-Porous Type Reservoir Using Parallel Computations -- Kinetic Modeling of Isobutane Alkylation with Mixed C4 Olefins and Sulfuric Acid as a Catalyst Using the Asynchronous Global Optimization Algorithm -- Simulation of Nonstationary Thermal Fields in Permafrost Using Multicore Processors -- High-Performance Calculations for Modeling the Propagation of Allergenic Plant Pollen in an Atmospheric Boundary Layer.
Keywords: Computer systems; Computer System Implementation